Design and Deployment of an Uninterruptable Power Supply Utilizing a Solar PV System for Tilapia Aquaculture Farm in Sabah, Malaysia - Abdul Rahman, Rahman; M. A., Ismail; Suffia, Misaran; Fadzlita, Tamiri; Nuramalina, Bohari; Sherena, Sar‑ee (UPT Penerbitan Universitas Jember, Indonesia, 2025)
Continuous power supply is essential for maintaining operational stability of indoor aquaculture farms to protect their mortality. This paper examines the feasibility and performance of a 0.83 kWp stand alone solar PV system for providing an uninterrupted power supply to a 185.8 m2 indoor tilapia farm located in Sabah, Malaysia (latitude: 6.03º N, longitude: 116.30ºE). Concerning these aspects, the system was designed specifically to operate critical equipment aerators and water pump within about five hours every week during grid power interruptions. The site was evaluated through the Global Solar Atlas showing an average global horizontal irradiation of 4.74 kWh/m2/day. Using on-site load analysis, the demand was found to be 1,750 Wh/week. The system consists of two 415 Wp PV modules connected in series, a 2.4 kWh lithium-ion battery, and a 2.4 kW inverter/charger scaled up to meet the demand while considering system losses. In addition, the virtual simulation of the system confirmed the average daily energy production to be about 2.95 kWh, which exceeds the demand by approximately 69%, hence allowing operation within the scheduled grid power outage. This research work highlights the technical feasibility along operational benefits resulting from small-scale PV deployment at aquaculture in tropical region, offering a scalable framework for improving energy reliability and sustainability in rural environments.